Relationship between Teacher Communication Patterns and Students' BTQ Ability - Mulianah, Sri; Hidayat, Wahyu; Darmiati, Darmiati (Universitas Muhammadiyah Magelang, 2021)
Poor communication patterns between teachers and students in learning to read and write the Qur'an or Baca Tulis Qur’an (BTQ) negatively impact students' ability to understand the message conveyed. Therefore, this research aims to determine the relationship or correlation between teacher communication patterns and BTQ ability of junior high school students. This is a quantitative associative research with the random sampling technique used to determine the sample size of 300 students. Data were collected through questionnaires and documentation, while descriptive and inferential methods using the product-moment correlation formula were utilized for analysis. The results indicate that (1) 270 students (90%) out of 300 communicated effectively with teachers, therefore, the communication patterns relationship between them is in the good category. (2) 210 students (70.0%) have BTQ ability in Islamic education, therefore, their ability to read and write is in the good category. (3) there is a positive relationship between teacher communication patterns and students' BTQ ability with 80.1% and 19% in Islamic education and other variables not observed in this research